Injectable hydrogel microspheres for sustained gene delivery of antisense oligonucleotides to restore the expression of dystrophin protein in duchenne muscular dystrophy. (5th March 2022) - Attias Cohen, Shani; Simaan-Yameen, Haneen; Fuoco, Claudia; Gargioli, Cesare; Seliktar, Dror
Graphical abstract: Highlights: We developed an injectable hydrogel delivery vehicle, namely PF microspheres, for the sustained delivery of antisense oligonucleotides (AONs), when applying an exon-skipping approach to treat Duchenne muscular dystrophy (DMD). The in vitro release of the AONs was sustained for several weeks, concurrent to the degradation of the PF microspheres, and the released AONs were incorporated into murine myoblasts from mdx dystrophic mouse model. The AON-laden PF microspheres were administered intramuscularly into the tibialis anterior muscle of mdx dystrophic mice to reveal a marked reduction in both inflammation and fibrosis scores after 30 days. The microspheres proved effective by improving the AON pharmacokinetic properties, increasing their stability, and greatly decreasing the overall administered dosage. This study is significant in that it provides the medical community with an injectable microsphere delivery system capable of controlled release of AONs for treating DMD. Abstract: Duchenne muscular dystrophy (DMD) is a genetic disease characterized by the absence of functional dystrophin protein. Antisense oligonucleotides (AONs) exon-skipping is one of the most promising therapeutic strategies for the treatment of DMD. In order to increase stability and enhance the cellular uptake of the AONs, polymeric carriers have been used as an efficient approach for AON delivery. Here we designed a hydrogel-based strategy for encapsulation of therapeutic, chemically modified 2′-O-methyl phosphorothioate (2OMePs) AONs in injectable PEG-Fibrinogen (PF) microspheres. The PF microspheres function as a controlled-release system that can improve the pharmacokinetic properties, increase their stability and greatly decrease the overall administered dosage. The PF microspheres were fabricated using a dual photo-initiator emulsion method: they were successfully loaded with 2OMePs AONs and proved to be injectable and cytocompatible with in vitro cultures of C2C12 mouse myoblasts. The in vitro release of the 2OMePs AONs was sustained for several weeks, concurrent to the degradation of the PF hydrogel. The released 2OMePs AONs were incorporated into murine myoblasts from an mdx dystrophic mouse model, showing sustained cellular uptake achieved using this controlled release strategy. The AON-laden PF microspheres were also administered intramuscularly into the tibialis anterior muscle of mdx dystrophic mice. Histology after 30 days revealed a marked reduction in both inflammation and fibrosis scores when compared to naked AON controls. The study concludes that the injectable PF microspheres are a good candidate for the controlled release of 2OMePs AONs, particularly in the development of better modalities for treating DMD.